The Great Leap: Transitional Experience of Public School Teachers to the New Normal System of Education - dela Cruz, Gabrielle A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study aimed to describe how teachers gave meaning to their transition experience to the new normal landscape of education amid the COVID 19 crisis. Using Transcendental phenomenological approach to qualitative research by Moustakas (1994), the researcher sought to explore the life world of seven (7) public school teachers who participated in individual interviews and focus group discussions and provided formal responses for the study. Interview data were collected and analyzed to offer textural-structural descriptions and the essence of the transition experience. The result revealed thirty-eight (38) significant statements forming six (6) essential themes: 1.) feeling of anxiety and stress, 2.) commitment to work, 3.) high volume workload, 4.) communication constraints, 5.) strong support system, and 6.) embracing new technologies which emerged among participants’ testimonies. These themes were further elaborated through textural and structural descriptions capturing the essence of the experience. In turn, emerging themes and underlying universal structures were used in developing a systematic framework named LEAP Transition Model to facilitate an understanding of teachers in transition and to provide them with the help they needed to cope better with the changes brought by an education crisis. The implications were discussed and further recommendations were made along with suggestions for future research.